Medicinal Plants Biodiversity and Drugs - Rai, Mahendra; Ed (CRC Press, 2012)
This volume provides a contemporary overview of new strategies for traditional medicine development, of the importance of cataloging ethnomedical information, of determining the active principles, and of examining the genetic diversity and range of actions of traditional medicines. It discusses the challenges of using traditional medicines for diseases where access to modern medicine is limited, and the research areas needed to improve quality, safety and efficacy for enhancing healthcare. The book affirms the importance of traditional medicines as an essential and integral component of health.